EFFECT OF DIFFERENTS TYPES OF POTASSIUM FERTILIZATION ON THE YIELDING OF GREENHOUSE TOMATOES GROWN IN VARIOUS SUBSTRATES - Zbigniew Jarosz (Acta Scientiarum Polonorum: Hortorum Cultus, 2006)
The investigation was carried out in greenhouse with tomato cv. ’Cunero F1’ grown in rockwool, peat and sand substrates with fertigation system without recirculation. In this research nutrient liquid with or without chlorine was tested. The experiment showed no significant differences on the total, marketable and unmarketable yield of plants fertilized nutrient liquid with or without chlorine. The highest yielding of tomato in rockwool, while lowest in sand substrates was detected. The higher weight of one tomato fruit in peat substrate, compare to sand, was observed. Both substrates and kind of potassium fertilizing had no significant effect on the number fruits per plant.